Historia, pamięć historyczna czy tożsamość? El „Arrano beltza”: znak Normanów - Pérez, Francisco José Alfaro (Studia Europaea Gnesnensia, 2016)
This text discusses the origins of the sign of the black eagle (arrano beltza) in the Basque universe. The analysis demonstrates the roots of the emblem, which stems from the Frankish world and evinces its contribution to the 12th-century Iberian reconquest.